Development of a conformal slot antenna for UAVs - Jiang, Zeyu (Nanyang Technological University, 2024)
Antenna, as an indispensable component of UAVs, has a great impact on the efficiency of information transmission. This project compared various slot antennas and aimed to find a conformal slot antenna with high gain and low profile. The designs and simulations were conducted in ANSYS HFSS. Parameter sweep was utilized to adjust the length, width and location of slots and microstrip line, in order to help the slot antennas meet the requirements of impedance match and achieve better performances. Four kinds of slot antennas were operated at an input frequency of 2.5 GHz. Microstrip feed slot antenna is the most fundamental slot antenna with bias-fed feeding method. Cavity backed slot antenna makes the radiation only on a vertical downward direction. It also achieves the highest realized gain, 6.92 dB. Wide slot antenna has the largest bandwidth, 1 GHz. Triple slot antenna was built to simulate like a simple antenna array. Overall, all the designed slot antennas have good radiation patterns and low VSWR at the operated frequency, which are conformal to install on UAVs. The realized gain can still be enhanced by parameter selection in the future.